The mosses of Mount Lumaku, Sipitang, Sabah, Malaysia - Monica Suleiman; Fadzilah Awang Kanak; Dunstan P. Masundang (2011)
A checklist of mosses collected from Mount Lumaku is presented. In total, there are 127 species, two varieties and one subspecies in 63 genera and 27 families of mosses recorded from this mountain, representing ca. 18 % of the reported taxa of mosses in Borneo. The largest family was Sematophyllaceae with 18 species and one variety, followed by Calymperaceae with 12 species and Dicranaceae with 11 species. Macromitrium salakanum Müll.Hal. is a new addition to the Borneon moss flora, while Distichophyllum santosii E.B.Bartram and Mitthyridium constrictum Sull. (H.Rob.) are new records for Sabah.